Gender Approach In Islamic Views - Saeful Anwar; M.Irfan Rosfiana; Sukma Hendrian (Asian Journal of Social and Humanities, 2023)
Gender equality is a phenomenon that is echoed by some audiences, ranging from academics, activists to politicians or public officials. Even though this discourse has been around for a long time, this discussion of gender has always been present at all times with various new discussions as well as old ones that have been updated. So whether you realize it or not, women and the issue of gender equality have recently become very interesting and lively for discussion, especially when it is related to Islamic discourse, where women in Islamic history did have an important position in various social, cultural, and social changes. economy, and even politics in this country. On this occasion, the author conducted a comparative analysis of the gender approach in Islamic studies by focusing on the discussion on the implementation of gender in society by searching books (research libraries) related to this discussion. Comparative analysis technique is a technique used to compare events that occurred when researchers analyzed these events and carried them out continuously throughout the research. Gender is used to identify differences between men and women from a socio-cultural perspective. While sex is used to identify differences between men and women in terms of biological anatomy. In addition, the relationship between women and men in Islam can in principle be called synonymous with talking about the equal partnership of men and women. Because in Islam in principle the relationship between the two sexes is equal before Allah (khaliq).